Developing of Recipe Books Based On Local Fruits - Mohd Razi, Nur Shazratul Syazwani; Md Sahak, Adibah Aishah; Abdul Rahman, Abdul Wafi; Mohd Yazid, Nur Diyana (Research and Innovation in Technical and Vocational Education and Training, 2022)
This study aims to develop a recipe book for desserts based on local fruits as a teaching aid for the field of Catering. With this recipe book, lecturers can use it as a teaching aid and to be used as a reference and guidance for Catering students. In addition, this recipe book can be used to facilitate the teaching and learning process and students can learn independently. The objective of this study to develop a local fruit-based dessert’s recipe book and identify the suitability of the recipe books among the teaching staff. In this study, the researcher used the ADDIE model as a guide in developing this recipe book. The research method used is a quantitative method using a questionnaire instrument to obtain research data. Respondents in this study are ten experts who are experienced in teaching in this field. Data and feedback were obtained from questionnaires and expert validation. Therefore, the developed recipe book has received expert approval in terms of recipe book development, content suitability and recipe book design elements. In conclusion, the development of recipe books as teaching aids is suitable for development based on the feedback of experts. It is hoped that this book could enrich the teaching and learning process.